UAV based smart grazing: a prototype of space-air-ground integrated grazing IoT networks in Qinghai-Tibet plateau - Ji Li; Min Ling; Bin Fu; Yugang Dong; Weiqiang Mo; Kai Lin; Fangyuan Yuan (Discover Internet of Things)
Abstract Smart grazing is a relatively difficult field of digital agriculture. Restricted by the geographical conditions of pastures, poor network infrastructure and low economic output, conventional IoT systems are difficult to apply in the field of grazing. In this paper, we propose the Space-Air-Ground integrated Grazing IoT(SAG-GIoT) system based on the background of yak grazing production in the Qinghai-Tibet Plateau, and define three smart grazing management application scenarios: (1) daily grazing supervision, (2) UAV grazing, (3) searching for yaks. To this end, we have designed the three-tier technical architecture of SAG-GIoT, and developed collar, base station and grazing management system. We designed the all-terrain network service scheme with the BeiDou Satellite-Base Station Sender(BDS-BSS) and Small Base Stations(SBSs), and verified the daily grazing supervision test in long-term. UAV grazing test was carried out in pasture, and a flexible communication networking was realized through the UAV Based Sation(UAV-BS). With the guidance of UAV searching and APP positioning, taking Handled Base Stations(HBSs) in hand, we quickly and accurately find the lost yaks. SAG-GIoT system is characterized as low cost, flexible deployment and global service, and has broad application prospects.